LEXICAL INTERFERENCE IN DAILY ENGLISH COMMUNICATION: A STUDY OF UZBEK NATIVE SPEAKERS (SCIENCE TIME JOURNAL, 2026)
This study is dedicated to examining the phenomenon of lexical and semantic interference occurring in the speech of English learners who speak Uzbek. The main goal of the research is to identify and analyze the types of interference observed in the students' speech. The study was conducted using a qualitative approach, and data were collected through direct observation in a natural classroom setting without special assignments. The results show that students' speech mainly exhibits lexical interference, semantic interference, and cases of "false friends." Students often rely on the structure of their native language (Uzbek) when constructing sentences in English, which leads to incorrect word choice and meaning distortion. These findings align with previously proposed theoretical views on language interference. Overall, the research results indicate that interference is a significant problem for English learners who speak Uzbek. Therefore, it is recommended to strengthen context-based approaches in the teaching process and pay special attention to "false friends" words.